1985
DOI: 10.1111/j.1475-097x.1985.tb00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia metabolism during exercise in man

Abstract: Physical exercise is accompanied by increased plasma levels of ammonia but it is not known whether this rise primarily reflects accelerated formation in muscle or decreased removal by the liver. Consequently, leg and splanchnic exchange of ammonia was examined, using the catheter technique, in 11 healthy subjects at rest, during three consecutive 15 min periods of bicycle exercise at gradually increasing work loads (35%, 55% and 80% of maximum oxygen uptake) and for 60 min during post-exercise recovery. The ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 21 publications
1
67
1
3
Order By: Relevance
“…During exercise, muscle ammonia is mainly derived from increased activity of the purine nucleotide cycle." Ammonia release from skeletal muscle during exercise has also been described by Eriksson et al 34 Katz et .al. 35 calculated a release rate of about 130 mmol124 h at maximal workload.…”
Section: Lungmentioning
confidence: 77%
“…During exercise, muscle ammonia is mainly derived from increased activity of the purine nucleotide cycle." Ammonia release from skeletal muscle during exercise has also been described by Eriksson et al 34 Katz et .al. 35 calculated a release rate of about 130 mmol124 h at maximal workload.…”
Section: Lungmentioning
confidence: 77%
“…Furthermore, isometric contraction exercise with two-thirds maximum voluntary contraction to fatigue decreased glutamate levels, but increased alanine and pyruvate levels in muscles 25) . Eriksson et al 26) conducted a detailed investigation of the release and uptake of free amino acids in muscles by monitoring arteriovenous oxygen differences during cycle ergometer exercise with gradually increasing workloads (30%, 55%, and 80% of V ・ O2max: 15 min at each workload level). They found that the amount of alanine released from exercising muscles increased significantly by 2.7-fold and 8.9-fold during exercise with a load of 55% and 80% of V ・ O2max, respectively, compared with pre-exercise levels.…”
Section: Muscle Fiber Type Differencesmentioning
confidence: 99%
“…300% increase at 55% Vo,,, and 900% at 80% VO,,~, Eriksson et al 1985). The increase in glutamine release is less and in any case is partly at the expense of intramuscular glutamate (Eriksson et al 1985;Katz et al 1986;Henriksson, 1991). Trained athletes tend to oxidize more fat and less carbohydrate than the general population; therefore, because amino acid oxidation roughly matches glycogen utilization, alanine production (an indicator of amino acid oxidation) by trained athletes is less (see Rennie et al 1994).…”
Section: Nature Of Any Increased Lossesmentioning
confidence: 99%